Multiplex PCR of bcr-abl fusion transcripts in Philadelphia positive acute lymphoblastic leukemia. - Lee, A; Kirk, J; Edmands, S; Radich, J (Genome Research, 1995)
We describe a multiplex PCR assay for the detection of bcr-abl fusion mRNA in Philadelphia chromosome positive acute lymphoblastic leukemia (Ph + ALL). The assay provides a quick method for screening p190 (e1:a2) and p210 (b2:a2 or b3:a2) bcr-abl mRNAs simultaneously. The assay proves to be highly sensitive with detection of as little as one positive bcr-abl-expressing cell in a background of 10(5) negative bcr-abl cells. Bone marrow and peripheral blood specimens from six patients were in total accordance when run by multiplex PCR and by the single primer PCR approach. The multiplex bcr-abl assay may prove to be highly useful for screening newly diagnosed patients with ALL for the bcr-abl fusion transcript and in following the course of disease during therapy.